Sosialisasi Tentang Bahaya Kenakalan Remaja pada Anak Panti Yayasan Bantuan Anak Indonesia Internasional (YBAII): - - Endang Hutapea; Novani Ramahdani; Gabriel, Gabriel; Daffa Tegar; Puput Bulolo (Yayasan Literasi Sains Indonesia, 2023)
The current social problem is the problem of juvenile delinquency, the impact arising from juvenile delinquency behavior and wise use of social media among adolescents, namely juvenile delinquency and the use of social media. As we know that there are many bad effects of juvenile delinquency and tend to be negative as well, promiscuity that causes free sex can be fatal to health. Free sex can occur because of the influence of the environment and one's wrong choice of environment in which to hang out. Juvenile delinquency is all behavior that deviates from the norms and values of criminal law committed by adolescents. This behavior can be detrimental to himself and those around him. The negative impacts of juvenile delinquency also vary, ranging from mild ones, such as disturbing the order and tranquility of the environment, to more extreme levels. So in this case we chose the topic for this socialization so that orphanage children don't get caught up in juvenile delinquency. Our goal is to socialize so that the orphans of the Indonesian International Child Assistance Foundation (YBAII) do not commit juvenile delinquency or keep the orphans away from negative things from their surroundings so that they are always on the right path and do not violate existing norms.